The Fund Agreement in the Court, Vol. IV - Gold, Joseph (Washington, D.C. : International Monetary Fund, 1989)
Written by Joseph Gold, former General Counsel and now Senior Consultant at the IMF, these volumes contain discussions of the ever-increasing body of cases in which the Articles have had bearing on issues before the courts.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet